Evaluation of the Interference of Hemoglobin Variant J-Bangkok on Glycated Hemoglobin (HbA1c) Measurement by Five Different Methods - Wen, Dong-Mei; Xu, Sheng-Nan; Wang, Wei-Jia; Zhang, Xiu-Ming; Suo, Ming-Huan; Zhang, De-Cai (Experimental and Clinical Endocrinology & Diabetes, 2017)
Objective The interference of the hemoglobin variant (Hb J-Bangkok) was evaluated on 4 different glycated hemoglobin assays and compared with a reference immuno assay.Methods An overall test of coincidence of 2 least-squares linear regression lines was performed to determine whether the presence of Hb J-Bangkok caused a statistically significant difference in HbA1c results compared with a reference immuno assay. Statistical analysis was performed on the difference of the estimated average glucose calculated from HbA1c values and fasting plasma glucose in the Hb J-Bangkok variant group using the different detection systems. Deming regression analysis was used to determinate whether Hb J-Bangkok had a significant interference on HbA1c results using an HbA1c±10% relative bias at 6% and 9% HbA1c as evaluation limits.Results Turbidimetric inhibition immunoassay method, and enzymatic methods were not affected by Hb J-Bangkok. However, Hb J-Bangkok showed statistically significant interference to the two ion-exchange high-performance liquid chromatography methods.Conclusion When performing HbA1c tests, clinical laboratory personnel should identify the Hb variant and select the appropriate methods or use alternative indicators.
Keywords: hemoglobin variant; Hb J-Bangkok; glycated hemoglobin; HbA1c; interference